2011
DOI: 10.3109/00365599.2011.609832
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lymph-node dissection in patients undergoing radical cystectomy following previous oncological treatment for bladder cancer

Abstract: LND in the previously irradiated pelvis may be difficult and remains controversial. Because of a high risk of vital tumours cells within the removed lymph nodes despite chemotherapy, extended LND should be performed in patients with non-regional lymph-node metastasis following preoperative chemotherapy. In patients with fixed tumours and minimal response to chemotherapy and in patients with visceral metastases, RC should be attempted for palliative reasons only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Pathologic complete response of the primary tumor and lymph nodes (LNs) on histopathology is a strong predictor of survival [2]; however, the prognosis for patients with persisting LN involvement is poor [3, 4]. Partial responders (mPRs) or non-responders (mNRs) to NAIC might not benefit from subsequent radical cystectomy [5]; instead, early alternative treatment pathways such as radiotherapy may be more effective. Early monitoring of the primary tumor and LN response to NAIC is therefore crucial, yet current treatment pathways do not always include imaging evaluation following NAIC, and radical cystectomy is performed regardless of the response to NAIC.…”
Section: Introductionmentioning
confidence: 99%
“…Pathologic complete response of the primary tumor and lymph nodes (LNs) on histopathology is a strong predictor of survival [2]; however, the prognosis for patients with persisting LN involvement is poor [3, 4]. Partial responders (mPRs) or non-responders (mNRs) to NAIC might not benefit from subsequent radical cystectomy [5]; instead, early alternative treatment pathways such as radiotherapy may be more effective. Early monitoring of the primary tumor and LN response to NAIC is therefore crucial, yet current treatment pathways do not always include imaging evaluation following NAIC, and radical cystectomy is performed regardless of the response to NAIC.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence supports the use of cisplatinbased induction chemotherapy in LN-positive and locally advanced disease, both to target micrometastases and to induce a regression in macroscopic tumour burden before RC and LN dissection (LND) [3][4][5][6]. In this setting, chemosensitivity is paramount because patients with a poor response have significantly worse outcomes after induction chemotherapy and RC [3], and it has been suggested that RC should be performed only in patients with a good response to induction chemotherapy [7]. Given the demography of the elderly population affected by bladder cancer and the toxicity of cisplatin-based induction chemotherapy, a method for earlier identification of the chemosensitive subset of patients would enable more individualised treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Maybe more importantly: can patients who do not respond or, even worse, progress under chemotherapy, be identified reliably? Their prognosis is dismal and it has been suggested that surgery has no therapeutic value for these patients [4]. Alternative second line therapies (experimental therapies, immunotherapy) or palliative treatment instead of surgery should be offered to patients with persisting LN metastases that are unresponsive to chemotherapy.…”
mentioning
confidence: 99%